Isidore of Seville and the “Liber Iudiciorum“ - Kelly, Michael J., author.
1 online resource.
Keywords: Isidore of Seville and the “Liber Iudiciorum“ establishes a novel framework for re-interpreting the Liber Iudiciorum (LI), the law-code issued in Toledo by the Visigothic king Recceswinth (649/653-672) in 654. The LI was a manifestation of a vibrant dialectical situation, particularly between two networks of authority, Isidore-Seville and Toledo-Agali, a defining characteristic of the discourse coloring the fabric of writing in Hispania, c. 600-660. To more fully imagine the meaning, significance and purposes of the LI , this book elicits this cooperative competition through a series of four case-studies on writing in the period. In addition to offering an alternative historiography for the LI , this book expands the corpus of “Visigothic Literature“ and introduces what the author refers to as “Gothstalgie.“.